PROSES BERPIKIR SISWA PADA TAHAPAN DASALITNUM DALAM PEMBELAJARAN NUMERASI KONTEN BILANGAN PADA SISWA KELAS V SD NEGERI BURAEN 1 - Yunita Makdalena Kollan; Helti Lygia Mampouwr; Wahyu Hari Kristiyanto (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores the thinking processes of Class V students at SDN Buraen 1, South Amarasi District, Kupang Regency, through the 10-step numeracy learning model called Dasalitnum. Using a qualitative approach, the research involved nine students representing the red, yellow, and green zones based on their mastery of mathematical concepts. Data were collected during Mathematics lessons in the odd semester of 2024/2025. The findings indicate that the Dasalitnum approach effectively enhances students’ thinking processes in number material. Red zone students progressed from guessing to understanding problems with guidance, yellow zone students began to think independently and select solution strategies, while green zone students demonstrated critical and reflective thinking. Overall, Dasalitnum supports students in contextual problem understanding, identifying key information, evaluating, and revising solutions. This strategy strengthens numerical mindsets and is relevant for schools with low numeracy achievement.